2018
DOI: 10.1002/jpen.1470
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nutrition Supplementation on Osmolality of Expressed Human Milk

Abstract: Background Provision of human milk to premature infants optimizes outcomes, but it must be supplemented to meet their nutrient and caloric requirements for growth. Our objective was to quantify the osmolality of human milk mixed with commercially available human milk fortifiers (HMF) and powdered infant formula, as currently fed to premature infants, simulating standard neonatal intensive care unit feeding practices for mixing and refrigerator storage. Methods Expressed human milk (EHM) samples obtained from m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…Subsequently, we studied the effect of HMFs on osmotic concentration. In agreement with previous publications, we observed that osmolality of BM increases significantly upon fortification and that osmolality of fortified BM increases with time unlike that of plain BM, which remains constant [22,23,25,27,29]. Lamport et al studied two liquid HMFs and four powder infant formulas to achieve different caloric targets and they obtained osmolalities higher than 450 mOsm/kg as we have observed.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Subsequently, we studied the effect of HMFs on osmotic concentration. In agreement with previous publications, we observed that osmolality of BM increases significantly upon fortification and that osmolality of fortified BM increases with time unlike that of plain BM, which remains constant [22,23,25,27,29]. Lamport et al studied two liquid HMFs and four powder infant formulas to achieve different caloric targets and they obtained osmolalities higher than 450 mOsm/kg as we have observed.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, Aceti et al showed that values below 450 mOsm/kg do not result into an increase in reflux in premature newborns [38]. Nevertheless, in the last years, Miyake et al and Lamport et al had raised the need to reevaluate the maximum osmolality recommended by the APP [24,25]. In our hands, BM fortified with HMF Almirón Fortifier1 or NANFM851 induced osmolalites clearly over the limit recommended by AAP.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…In our study, we investigated how target fortification can modify the osmolality of pasteurised donor human milk and raw mature milk over time. The osmolality of human milk before fortification was on average of 289 mOsm/L, which is comparable to the other results in the literature (26–30). After target fortification (based on the analysis of breast milk composition and addition of adequate individual targeted macronutrients), we found that the osmolality increased up to the 30% immediately after fortification.…”
Section: Discussionsupporting
confidence: 88%